ANALYSIS OF THE RELATIONSHIP OF INVENTIVE THINKING AND SCIENCE-RELATED ATTITUDE - Eka Ad'hiya; Maefa Eka Haryani; Rodi Edi; Diah Kartika Sari; Nadila Nur Savitri (University of Bengkulu, 2024)
This study aims to analyze the relationship between inventive thinking (IT) and science-related attitude (SRA). This study is a quantitative study with a cross-sectional study design. Participants in this study were 109 chemistry education students, Sriwijaya University. The instruments used in this study were an adaptation of the inventive thinking measurement instrument and an adaptation of the science-related attitude (TOSRA) measurement instrument. Data analysis was carried out using Rasch Analysis to determine the validity and reliability of the instrument, as well as to measure inventive thinking and science-related attitude, which was then analyzed using Pearson correlation analysis. The results of the validity analysis showed that the MNSQ Outfit of both instruments (IT = 1.01 and SRA = 1) was in the range of 0.5-1.5 which was classified as valid or could measure what was to be measured well. The reliability of both instruments (IT = 0.98 and SRA = 0.99) was in the range> 0.94 which was classified as special. The results of the analysis of the relationship between inventive thinking and science-related attitude show that r = 0.273 is included in the low category. This shows that the relationship between science-related students and inventive thinking is low, or in other words there is no close relationship between inventive thinking ability and science-related students. The results of the Pearson correlation analysis also show a positive sign. This shows that the relationship between inventive thinking and science-related students is also positive, or not contradictory.